2020
DOI: 10.3390/agronomy10070973
|View full text |Cite
|
Sign up to set email alerts
|

Defining Targets for Reversing Declines of Soil Carbon in High-Intensity Arable Cropping

Abstract: Soil organic carbon (SOC) is declining globally due to intensification of agriculture. Reversing declines should reduce soil erosion, maintain yields, raise the soil’s atmospheric carbon sink, and improve habitat for biodiversity. Commercial fields were sampled in a diverse European Atlantic zone cropland to relate SOC status to cropping intensity and to define a realistic target for restoration. SOC (%C by mass) decreased from 4% to 2% as the proportion of high-intensity crops increased from zero to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The cropping systems are now at a crucial point. The main conclusion from the present work and related studies [33,36,40,64,67] is that conflicts between restoring soil carbon, minimizing the environmental footprint of nitrogen fertiliser, and maintaining yield or closing the yield gap are not resolvable in current, highly intensified cereal production systems. Major transitions to regenerative practices are needed, in particular the inclusion of more legumes and grass in rotation or as mixtures with cereals.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The cropping systems are now at a crucial point. The main conclusion from the present work and related studies [33,36,40,64,67] is that conflicts between restoring soil carbon, minimizing the environmental footprint of nitrogen fertiliser, and maintaining yield or closing the yield gap are not resolvable in current, highly intensified cereal production systems. Major transitions to regenerative practices are needed, in particular the inclusion of more legumes and grass in rotation or as mixtures with cereals.…”
Section: Discussionmentioning
confidence: 77%
“…Samples of soil and plants were taken at three points (loci) along three transects running over 100 m into a field, in total nine sample loci per field. Soil at each locus was mixed to a depth of 0.25 m, and a sample taken, dried in the laboratory, and processed for %C and %N by weight through an Element Analyser, as in previous studies [ 40 , 67 ] and adjusted by soil bulk density [ 36 ] to estimate C and N mass per unit field area, termed here C-soil and N-soil, respectively. These measures are not intended to estimate total C and N content of the soil, but C and N the layer of soil that is routinely tilled and fertilised, and in which there is active germination and root growth.…”
Section: Methodsmentioning
confidence: 99%
“…For a detailed comprehension of the SOC changes, the authors recommended a combination of measurements at different scales. Squire et al [43] defined targets for reversing declines in SOC in high-intensity arable cropping systems in the European Atlantic zone. The authors indicated that an achievable SOC target of slightly above 3% was defined for high-intensity sites.…”
Section: Monitoringmentioning
confidence: 99%
“…Design at these scales relies on facilitative ex-farm gate value chain elements, including governance structures, being in place at the whole food system level. Best practice management options selected according to specific local soil and environmental conditions [59,265] can be combined to improve the efficiency of resource use by supporting the internal generation of products and regulation of services as described in [System components]. No single management approach can meet all the objectives required of production systems [266], so best practice options must be integrated to minimise the negative effects of trade-offs between components of the agroecosystem and optimise the potential for multiple benefits between them [31,267,268].…”
Section: Integrated Design For Multiple Benefitsmentioning
confidence: 99%
“…For each of the system components, 'safe limits' [269] for optimal system functioning need to be defined according to local soil, climatic and socio-economic conditions (e.g. targets of 3% soil carbon content [265] or 10% weed cover [180]) and assessed on a field-by-field basis to provide a yardstick against which to gauge declines, recoveries and the impacts of transitions to sustainable arable systems.…”
Section: Integrated Design For Multiple Benefitsmentioning
confidence: 99%